(untitled) (The Review of Diabetic Studies, 2024)
Temporomandibular disorders (TMD) are complex conditions involving the temporomandibular joint and associated structures. Management has shifted from a traditional biomedical approach focused on dental occlusion to a biopsychosocial model, emphasizing the importance of integrated, interdisciplinary care. This research paper analyzes the collaborative roles of dentists, dental assistants, and physical therapists in TMD management, highlighting the dentist’s role in diagnosis and orthopedics, the physical therapist’s expertise in rehabilitation and neuromuscular education, and the dental assistant’s function in patient support and compliance. It argues that integration across these disciplines enhances patient outcomes through combined therapeutic techniques, such as occlusal splint therapy and manual therapy. The paper also demonstrates that early interdisciplinary intervention can significantly reduce long-term costs associated with orofacial pain.